2007
DOI: 10.4049/jimmunol.178.3.1312
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil-Activating Protein of Helicobacter pylori Crosses Endothelia to Promote Neutrophil Adhesion In Vivo

Abstract: Helicobacter pylori induces an acute inflammatory response followed by a chronic infection of the human gastric mucosa characterized by infiltration of neutrophils/polymorphonuclear cells (PMNs) and mononuclear cells. The H. pylori neutrophil-activating protein (HP-NAP) activates PMNs, monocytes, and mast cells, and promotes PMN adherence to the endothelium in vitro. By using intravital microscopy analysis of rat mesenteric venules exposed to HP-NAP, we demonstrated, for the first time in vivo, that HP-NAP eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 60 publications
0
74
0
Order By: Relevance
“…HP-NAP also induces a Th1-polarized immune response by stimulating the secretion of IL-12 and IL-23 (12), and also other proinflammatory cytokines such as TNF-a and IL-8 (13). Most studies on HP-NAP have investigated its role on innate immunity (10,(14)(15)(16). But, to act as an anticancer agent, it needs to induce a potent and specific adaptive immune response.…”
mentioning
confidence: 99%
“…HP-NAP also induces a Th1-polarized immune response by stimulating the secretion of IL-12 and IL-23 (12), and also other proinflammatory cytokines such as TNF-a and IL-8 (13). Most studies on HP-NAP have investigated its role on innate immunity (10,(14)(15)(16). But, to act as an anticancer agent, it needs to induce a potent and specific adaptive immune response.…”
mentioning
confidence: 99%
“…H pylori colonization is followed by infiltration of neutrophils, macrophages and lymphocytes in gastric mucosa. The degree of mucosal damag e is closely associated with the extent of neutrophil infiltration [2][3][4] . Multiple bacterial virulence factors, such as vacA, cagA and lipopolysaccharide (LPS), can modulate H pylori-induced inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was not considered that in vivo the under-flow conditions may bias the effects observed in vitro. The first in vivo evidence that HP-NAP promotes leukocyte adhesion to the endothelium and the subsequent extravasation was obtained by applying intravital microscopy analysis to rat mesenteric venules topically exposed to HP-NAP (Polenghi et al, 2007). The same study showed that HP-NAP is effectively transported across the endothelium via intracellular route and a proportion of the protein remains bound to the endothelium after transcytosis, similarly to what was reported for the chemokine CXCL8 (Middleton et al, 1997).…”
Section: Effects Of Hp-nap On Neutrophils: Recruitment and Activationmentioning
confidence: 61%
“…b2 Integrins, which are crucial for the tight adhesion of leukocytes to the endothelium before extravasation, need also to be activated to acquire their ligandbinding capacity. Again HP-NAP shows a role since it induces a conformational change of b2 integrins, resulting in an increased affinity for the endothelial partner (Polenghi et al, 2007). Collectively these data suggest that HP-NAP, via its direct intervention, has a crucial role in recruiting leukocytes towards the infected area and therefore, in triggering the inflammation process.…”
Section: Effects Of Hp-nap On Neutrophils: Recruitment and Activationmentioning
confidence: 77%
See 1 more Smart Citation